Conflits linguistiques invisibles : une communauté romande au bord de la mer Noire - Natalia Bichurina (Revue des Langues Romanes)
The paper explores the concurrence between two Romance languages, Francoprovençal and French, in a winegrowers’ community on the Northern Black sea coast, called Chabag (Shabo). It was founded by migrants from the Swiss canton of Vaud in 1822. Alienated from Vaud, the Francoprovençal and French speaking community found itself in a State, or rather States, for which both languages were marginal. Therefore, the power relations between the two languages were negotiated almost exclusively within the community. The municipality of Chabag was first part of the Russian empire, then of the Kingdom of Romania (between 1917 and 1940-44) and later from the Soviet Union; today Shabo it is part of Ukraine. The analysis focuses on the metalinguistic discourse produced by social actors of various types (a local pastor and teacher, researchers from dominant cultures) and in diverse sociocultural and epistemological settings. Rare publications are compared with archival data from Saint Petersburg, Odessa and Bern.